European Dimension of National Parliaments in the European Union - Endre-Sandor Erdõdi (Romanian Journal of European Affairs)
The institutions of the member states have been changed in the European integration process through the transfer of a part of their political and economic competences to the European Union. The national parliaments made no exemptions from this rule, even if they did not observed the loss of sovereignty from the very beginning. But in the ’80 and in the post-Maastricht era they realised this phenomena and the related consequences. Since then we can observe a mobilisation of the national parliaments to exert an increased influence on the decision making process in the European Council and in the Council of the EU, in order to compensate their loss of competencies in the past. This article presents the main functions of the national parliaments and their role on European level and also tries to show the mechanisms by which they participate in defining European policies. Finally, some recommendations will be made related to the necessary measures to be taken by the Romanian Parliament in order to be an effective participant in the EU decision making process after the accession date.